2016
DOI: 10.1002/adhm.201500900
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning Facilitates the Long‐Term Growth and Analysis of iPSC‐Derived Individual Human Neurons and Neuronal Networks

Abstract: The discovery of induced pluripotent stem cells (iPSC) and their application to patient-specific disease models offers new opportunities for studying the pathophysiology of neurological disorders. However, current methods for culturing iPSC-derived neuronal cells result in clustering of neurons, which precludes the analysis of individual neurons and defined neuronal networks. To address this challenge, we developed cultures of human neurons on micropatterned surfaces that promote neuronal survival over extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Most culturing conditions for pure stem cell-derived neurons have been based on conditions for primary rodent, primate, and human neurons, and these conditions mostly underperform with stem cell-derived neurons. Different strategies to enable long-term cultures (~100 days) of stem cell or iPSC-derived neurons have been used, such as growing the neurons on micropatterned surfaces [33] and astrocyte co-culture [34]. It has also been shown that adding mouse neurons in addition to astrocytes significantly increases the maturity of induced stem cell-derived neurons [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most culturing conditions for pure stem cell-derived neurons have been based on conditions for primary rodent, primate, and human neurons, and these conditions mostly underperform with stem cell-derived neurons. Different strategies to enable long-term cultures (~100 days) of stem cell or iPSC-derived neurons have been used, such as growing the neurons on micropatterned surfaces [33] and astrocyte co-culture [34]. It has also been shown that adding mouse neurons in addition to astrocytes significantly increases the maturity of induced stem cell-derived neurons [9].…”
Section: Discussionmentioning
confidence: 99%
“…We successfully grew iNGNs in long-term cultures using astrocyte co-cultures and a simple defined protocol that results in functional neuronal networks. The astrocytes could be helping to “micropattern” the single iNGNs in our studies, since we observed no cell clustering, that hinders long-term cultures [33], and in this way act as physical support for the neurons. The astrocytes also exert their support through secreted factors that benefit neuron viability and synaptogenesis [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…These microfluidic devices have enabled studies of axonal injury 1517 , axon pathfinding 18 and cellular migration 19 . They have also been utilized to investigate synaptogenesis 20 and circuit connectivity 2124 . A compartmentalized model of synaptic competition has been devised allowing the study of differences in individual neurons by chemically treating one chamber and performing synapse counting in another 22 .…”
Section: Introductionmentioning
confidence: 99%
“…have demonstrated the use of optogenetics and calcium imaging as tools to evaluate neuronal communication in a compartmentalized device 21 . These approaches have provided a proof of concept for microfluidics as a strategy to compartmentalize culture in brain circuit studies, but thus far they have only used primary neuronal cultures or are limited to human induced neurons of a single subtype 24 . Furthermore, in most cases, they are not permissive to high-definition functional studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it should be noted that all of the observations made in the experiments only provide indirect evidence of whether the 18 M iPSCs were rejuvenated, as aging and senescence can be induced under certain culturing conditions. [34][35][36][37] To determine whether reprogramming of aged somatic cells could lead to rejuvenation, we sought to aggregate 18 M iPSCs and 2 M iPSCs with 8-cell-stage ICR mouse embryos to derive chimeric newborns. Aggregation was performed using three iPSC clones in each group.…”
Section: Discussionmentioning
confidence: 99%